The Effect of an Immersive Virtual Reality on Nasogastric Tube Feeding Skills and Self-efficacy Among Nursing Students - Rias, Yohanes Andy; Akasyah, Wildan; Apriyanto , Bagus Sholeh (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: Video-based learning as a preparatory method for nasogastric tube feeding is prevalent among nursing students. Interestingly, there is a growing interest in incorporating immersive virtual reality (IVR) simulators into educational practices. Aims of this study to examine the effect of an IVR on nasogastric tube feeding skills and self-efficacy among nursing students. Methods: A quasi experimental study with trial two-arm. 108 nursing students were recruited from two universities in Central Java. The IVR group (n=54) received nasogastric tube feeding skill practice through IVR, whereas the control group (n=54) watched a 15-minute video. Both groups received online nasogastric tube feeding lectures. The outcomes were nasogastric tube feeding skills and self-efficacy, with evaluated immediately before and after interventions. The Chi-square test, and independent t-test were employed. Results: The results indicated a considerable improvement in nasogastric tube feeding skills in the IVR and the video groups, with significant differences found between the two groups. Additionally, the group that utilized IVR demonstrated higher scores in self-efficacy compared to the group that used video, with statistically significant differences reported between the two groups. Conclusion: The IVR education and video enhanced the skills and self-efficacy. IVR can be recommended as an intervention to improve the quality of long-term education nursing care through technological advances.